DESCRIPTION OF KNOWLEDGE IN EXCLUSIVE BREASTFEEDING MOTHERS AT SUKOMULYO COMMUNITY HEALTH CENTER, GRESIK - Mardhika, Amellia; Altas, Rania Iqlima; Fadliyah, Lailatul; Sulpat, Emuliana; Tyas, Anestasia Pangestu Mei; Medawati, Riris (Journal of Vocational Nursing, 2022)
Introduction: Exclusive breastfeeding is essential in fulfilling children's nutritional status. Exclusive breastfeeding is closely related to the mother's knowledge about breastfeeding. Thus, it is necessary to identify the level of understanding of mothers about exclusive breastfeeding. This study aimed to describe the knowledge of mothers who breastfeed exclusively at Sukomulyo community health centre, Gresik. Methods: This study used a retrospective descriptive research design. This study's population were mothers with babies aged >6 to 12 months at the Sukomulyo community health centre. The sample in this study was 35 samples obtained through the purposive sampling technique. The data were collected by filling out questionnaires and analyzed using a frequency distribution table. Results: Mothers who gave exclusive breastfeeding found that the majority of mothers aged 20-35 years were 26 people (74.29%), the education level of mothers who graduated from high school was 18 people (51.43%), and mothers worked as housewives as many as 25 people (71.43%). Most of the mothers had a good level of knowledge, as many as 27 people (77%) and only one mother with less knowledge. Mothers with good knowledge mainly were owned by mothers aged 20-35, as many as 21 people (77.78%), mothers with a college education last as many as 15 people (55.56%), and housewives as many as 21 people (77.78%). Conclusions: Mothers aged 20-35 years with a university education background and housewives tend to breastfeed exclusively.